Failures of the classical optical theorem under arbitrary-shaped beam incidence in electromagnetism, acoustics, and quantum mechanics: motivation and a review - Gouesbet, Gérard; Marston, Philip L. (Frontiers in Physics, 2023)
The classical optical theorem states that for a wave propagating in a lossless medium and incident on a …nite scatterer, the extinction crosssection is proportional to the real part of the scattering amplitude in the forward direction. When developing a light scattering theory known as generalized Lorenz-Mie theory (GLMT), it has been a surprise to observe in 1982 that the optical theorem fails when the scatterer is illuminated by an arbitrary shaped beam. The extremely simple reason of that failure has been understood only in 2014 and published in 2016. This represents a more than three decades long story which, for reasons to be mentioned in the paper, is called a "wow" story. The opportunity of this story which pertains both to the history and philosophy of sciences is taken to provide a review of the optical theorem, under arbitrary shaped beam incidence, in electromagnetism, acoustics and quantum mechanics.